To solve the expression \(-4(3+120)+150\) by generating an equivalent expression using the Zero Power Rule, we can note that any non-zero number raised to the power of zero is equal to 1. This can be applied to the numbers \(12^0\) and \(15^0\):
The correct process would look like this:
- Recognize that \(120 = 12^1 + 12^0\), so \(12^0 = 1\).
- So, in the context of the expression, you can replace \(120\) with \(1\) (since \(12^0 = 1\)).
- This gives \(−4(3 + 1) + 1\).
Carrying out this:
\[ -4(3 + 12^0) + 15^0 = -4(3 + 1) + 1 = -4(4) + 1 = -16 + 1 = -15. \]
Thus, the correct response is:
\(−4(3+12^{0}) + 15^{0} = -4(3+1) + 1 = -4 \cdot 4 + 1 = -16 + 1 = -15.\)